Women Are at a Higher Risk of Chronic Metabolic Diseases Compared to Men With Increasing Body Mass Index in China - Wang, Xiao-He; Lin, Jing-Na; Liu, Guang-Zhong; Fan, Hai-Ming; Huang, Ya-Ping; Li, Chun-Jun; Yan, Hong-Yuan (Frontiers in Endocrinology, 2020)
Background: Chronic non-communicable diseases are the major causes of mortality in the world. However, few studies have investigated the association between multi-categories BMI and chronic diseases from perspective of sex stratification. This study aimed to investigate whether BMI-health risks associations differ by sex and explore a set of clinically useful and sex-sensitive BMI cut-off values. Methods: In total, 21,134 participants aged 19-65 years (60.4% men) from the Tianjin People's Hospital, Tianjin Union Medical Center-Health Management Center were recruited for this cross-sectional study. Sex-specific percentiles of BMI were calculated and divided into 11 categories according to the 2000 CDC growth charts. Health-related indicators, such as hyperglycemia, hypertension, non-alcoholic fatty liver diseases (NAFLD), hyperuricemia, etc., were used as dependent variables in this study. Statistical differences were tested by unpaired Mann–Whitney U-test and chi-squared test. Logistic regression models were used to examine the associations between BMI and health-related indicators. Results: The risk of hyperglycemia (OR: 1.67, 95%CI: 1.23-2.29), NAFLD (OR: 2.22, 95%CI: 1.74-2.85), hypertriglyceridemia (OR: 1.65, 95%CI: 1.28-2.12) and hyperuricemia (OR: 1.39, 95%CI: 1.12-1.72) in men began to increase significantly when BMI was in the range of 22.59-23.89 kg/m2. However, in women, the risk of hyperglycemia (OR: 3.02, 95%CI: 1.25-8.98) and hyperuricemia (OR: 1.94, 95%CI: 1.26-3.05) began to increase significantly when BMI was in the range of 22.76-23.62 kg/m2, and the risk of NAFLD (OR: 5.48, 95%CI: 2.49-14.47) began to increase significantly when BMI was in the range of 21.08-21.97 kg/m2. Besides, at the same BMI level, the risk of diseases in women were significantly higher than that in men, especially when BMI > 25 kg/m2. Conclusion: The risk of chronic diseases in women with overweight or obesity were significantly higher than that in men. Besides, the risk of chronic diseases also increased both in men and women when BMI was in the “normal” range (18.5-24 kg/m2), and the BMI cut-off values of women (21.08-21.97 kg/m2) was lower than that of men (22.59-23.89 kg/m2). The results indicated that the cut-off values of BMI for men and women should be defined separately when predicting the risk of chronic diseases.